Guidelines Aimed at Reducing the Risks of User Acceptance Delay in the Context of an IT Service Project Management Plan - Eun Joo Jeong; Ji Hwan Bae; Seung Ryul Jeong (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Delays in the user acceptance of information technology (IT) service projects in Korea have occurred frequently due to various risk factors. User acceptance delays may hinder the achievement of the client’s project objectives and cause schedule delays or cost overruns. Furthermore, the client may impose a delay charge and claim for additional damages, causing serious disputes between buyer and supplier. The main causes of user acceptance delays are unclear user requirements, changes in user requirements, poor-quality development outputs, excessive functional and non-functional errors, lack of user involvement, unclear user roles and responsibilities, and unclear criteria of user acceptance test.We help foster the timely completion of user acceptance by proposing a method of identifying the risk factors in user acceptance delay and creating a project management plan to weed out the identified risks. We propose a guideline for an IT service management plan that weeds out or lowers the risk factors well in advance. To validate the guideline’s utility, we apply it to IT service projects. The results show that the guideline is effective in identifying and removing risk factors affecting delays in the user acceptance of IT service projects.